2019
DOI: 10.2147/ott.s227482
|View full text |Cite
|
Sign up to set email alerts
|

<p>Long Noncoding RNA LINC00265 Targets EGFR and Promotes Deterioration of Colorectal Cancer: A Comprehensive Study Based on Data Mining and in vitro Validation</p>

Abstract: BackgroundLncRNAs are found to be aberrantly expressed in human cancers and could function as potential oncogenes or tumor suppressor genes. LINC00265 is a newly discovered LncRNA and its function in colorectal cancer (CRC) remains unknown.MethodsComprehensive bioinformatics analysis were performed to investigate the expression, clinical significance and potential biologic functions of LINC00265 in CRC based on the data from the Cancer Genome Atlas (TCGA). To further investigate the potential role of LINC00265… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…As expected, our data showed that LINC00265 was upregulated in GC tissues and cell lines. Additionally, it was observed that LINC00265 knockdown significantly restricted GC cell proliferation in vitro, similar to the previous studies in CRC 38 , suggesting that LINC00265 may serve as an oncogene in GC.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…As expected, our data showed that LINC00265 was upregulated in GC tissues and cell lines. Additionally, it was observed that LINC00265 knockdown significantly restricted GC cell proliferation in vitro, similar to the previous studies in CRC 38 , suggesting that LINC00265 may serve as an oncogene in GC.…”
Section: Discussionsupporting
confidence: 87%
“…It has been reported that LINC00265 was upregulated in CRC and played a key role in disease progression. For instance, Ge et al suggested that increased LINC00265 expression closely correlated with lymph node metastases and advanced pathological stage in CRC, and LINC00265 could promote HT29 cell proliferation and invasion by upregulating the expression of EGFR [ 37 ]. Sun et al also demonstrated that LINC00265 was upregulated in CRC and intimately correlated with poorer patient prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…14 Increasing evidence has demonstrated that a number of lncRNAs are dysregulated in CRC, contributing to CRC genesis and progression. [15][16][17] LncRNAs can execute cancer-inhibiting or cancer-promoting activities during CRC oncogenesis and are directly involved in several malignant processes. 18,19 MicroRNAs (MiRNAs) are a family of short noncoding RNA molecules with a length of approximately 17-24 nucleotides.…”
Section: Introductionmentioning
confidence: 99%
“…We believed that these 15 genes were key points in the regulation of the whole PPI network. We found that some genes were related to the proliferation and apoptosis of Colorectal cancer, such as EGFR, CDK2, CCN2 and BCL2L1 23 - 26 , and some were related to the prediction of chemotherapy for colorectal cancer, such as EGFR, TYMS 27 , 28 . Others, such as MMP9 29 , were associated with the metastasis of colorectal cancer.…”
Section: Discussionmentioning
confidence: 92%